2020
DOI: 10.1002/csc2.20144
|View full text |Cite
|
Sign up to set email alerts
|

In situ dry matter and crude protein disappearance dynamics in stockpiled limpograss

Abstract: Stockpiling warm‐season perennial grasses for winter grazing is an important management practice for beef cattle production systems in tropical and subtropical regions. Limpograss [Hemarthria altissima (Poir.) Stapf et C.E. Hubb.] has greater digestibility at late maturity than other commonly used warm‐season perennial grasses; however, decreased crude protein (CP) concentration may limit livestock performance. The objective of this study was to evaluate the in situ dry matter (DM) and CP ruminal disappearance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…In accordance with our study, Wallau et al. (2020) indicated that limpograss CP decreased linearly from 8 to 16 wk of stockpiling period.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…In accordance with our study, Wallau et al. (2020) indicated that limpograss CP decreased linearly from 8 to 16 wk of stockpiling period.…”
Section: Resultssupporting
confidence: 93%
“…This was probably because the average temperature in January 2017 was greater than in January 2016 (Table 1), resulting in the growth of new plant material with greater nutritive value. In accordance with our study, Wallau et al (2020) indicated that limpograss CP decreased linearly from 8 to 16 wk of stockpiling period.…”
Section: Stockpiling Periodmentioning
confidence: 99%
“…Studies report limpograss as a successful alternative to stockpiling pastures during the cold season or mild winters in subtropical regions (Quesenberry & Ocumpaugh, 1980). The use of stockpiled pasture in beef cattle production systems is a management practice that aims to extend the grazing season and reduce the need for costly supplements (Wallau et al., 2020). Limpograss has been widely planted in beef cattle operations in the southeastern United States due not only to cold tolerance, but also due to a slower decrease in digestibility with increasing plant maturity (Quesenberry et al., 2004; Vendramini et al., 2008; Wallau et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Wallau et al. (2020) evaluated the in‐situ kinetics of dry matter (DM) and the disappearance of crude protein (CP) from a stockpiled pasture of limpograss for 2 yr, and obtained an average forage accumulation variation of 5,300 and 7,700 kg ha −1 , between the start and end date of evaluation, respectively. In addition to a faster growth rate than bahiagrass ( Paspalum notatum Fluggé), a grass widely used in Florida, limpograss has similar leaf and stem digestibility (Pitman et al., 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation